Influence of polyaniline coated kenaf fiber on kenaf paper sheet - Abdullah Hisham, Nur Syafiqah (2015)
This paper reports the properties of newly developed electrically conductive natural fiber paper sheet made up of kenaf fiber (KF) incorporated with polyaniline coated kenaf fiber (KF-PANI). This study proposed on dispersion of conductive filler in different amount (wt %) into kenaf pulp for developing different electrical conductivity. The conductive sheet (KF/KF-PANI) revealed a percolation concentration at 25 wt% of KF-PANI. Its scanning electron micrograph showed good paper formation with no significant damages.